Superhydrophobic Surfaces Developed by Mimicking Hierarchical Surface Morphology of Lotus Leaf - Latthe, Sanjay S. (Molecules, 2014)
The lotus plant is recognized as a ‘King plant’ among all the natural water repellent plants due to its excellent non-wettability. The superhydrophobic surfaces exhibiting the famous ‘Lotus Effect’, along with extremely high water contact angle (>150°) and low sliding angle (<10°), have been broadly investigated and extensively applied on variety of substrates for potential self-cleaning and anti-corrosive applications. Since 1997, especially after the exploration of the surface micro/nanostructure and chemical composition of the lotus leaves by the two German botanists Barthlott and Neinhuis, many kinds of superhydrophobic surfaces mimicking the lotus leaf-like structure have been widely reported in the literature. This review article briefly describes the different wetting properties of the natural superhydrophobic lotus leaves and also provides a comprehensive state-of-the-art discussion on the extensive research carried out in the field of artificial superhydrophobic surfaces which are developed by mimicking the lotus leaf-like dual scale micro/nanostructure. This review article could be beneficial for both novice researchers in this area as well as the scientists who are currently working on non-wettable, superhydrophobic surfaces.